VIIIConference on the Utilization of Ultrasonic Methods for Studying the Properties of Condensed Matter – Zilina (Czechoslovakia) 1–4 september, 1982 - SOCZKIEWICZ, Eugeniusz (Archives of Acoustics, 1983)
VIII Conference on the Utilization of Ultrasonic Methods for Studying the Properties of Condensed Matter was held on 1-4 September, 1982 at Zilina (Czechoslovakia). The Conference was sponsored by the Physics Section of the Slovak Mathematicians and Physicists Association, the Acoustic Committe (Ultrasonics Subcommission) of the Czechoslovak Academy of Sciences, and organized by the Physics Department of the Technical University of Advanced Transport Engineering at Zilina, and Physics Institute of the Slovak Academy of Sciences in Bratislava. Assistant Prof. Dr. J. DURCEK was the chairman of the Organizing Committee of the Conference.